The Influence of Worship Facility Architectural Design and Perception Value on Shopping Mall Visitor Satisfaction: Religiosity as a Moderator Variable (Architecture Image Studies, 2025)
This study investigated the influence of architectural design of worship facilities, the value of emotional perception, and the value of social perception on the satisfaction of shopping mall visitors, with religiosity as a moderator variable. The study used a quantitative approach with Structural Equation Modeling - Partial Least Squares (SEM-PLS) involving 215 respondents. The study's results show that the Architectural Design of Worship Facilities has no significant influence on Satisfaction. The emotional perception value had the most decisive influence on satisfaction (coefficient 0.5448), while the social perception value was insignificant. Religiosity had a direct influence on satisfaction (coefficient of 0.3036), but did not moderate the relationships among the other variables. In contrast, the value of emotional perception has been shown to mediate the relationship between architectural design and visitor satisfaction. These findings underscore the importance of attending to the emotional aspect in designing mall worship facilities to create a positive experience for visitors. Mall managers are advised to improve design elements such as lighting and comfortable layouts, and to pay attention to spiritual aspects in the design of worship facilities to strengthen visitors' emotional and spiritual experience and increase their satisfaction levels.